Dual-variable control load-sensing system for multi-way valves in hilly and mountainous tractors - Yiwei Wu; Yuzhen Ruan; Jingyun Zhang; Shuai Wang; Lin Wang; Xiaoxiao Du; Xianghai Yan (PLoS ONE, 2025)
To tackle the challenges of severe pressure loss, mismatched flow supply and demand, and high flow demands at pump outlets commonly seen in multi-way valves of hilly and mountainous tractors, a load-independent flow distribution system was developed. This system combines an electro-hydraulic load-sensing pump with an independent flow distribution mechanism at the load port, resulting in a dual-variable load sensing system that integrates variable displacement and variable speed control. Using AMESim software, the core components and system model of the dual-variable load sensing system were built. Considering the operational characteristics of the multi-way valve, a load-sensitive variable pump with pressure differential and displacement detection was employed as the feedback control unit. The system incorporates a valve post-compensation mechanism and a three-position, six-way electro-hydraulic proportional directional valve. Additionally, a self-adjusting motor control method for pressure differential adaptation was introduced to regulate system pressure under high-load conditions. Simulation analyses of the system performance revealed that the design effectively boosts energy efficiency, achieving average energy savings of 20% and reaching up to 50% under optimal conditions, while keeping pressure fluctuations at the valve port within a 5% margin. By employing dual-variable load sensing technology, this system substantially improves the energy efficiency and operational effectiveness of multi-way valves while maintaining stable pressure throughout the operation. The design offers a reliable technical framework for the development and optimization of multi-way valves in hilly and mountainous tractors.